(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this article, necessary condition for existence of characteristic roots of Neutral Delay Differential equation to study the stability of a nonlinear system of a mass-spring-damper connected to a pendulum is derived from an real-time dynamic sub structuring model and illustrated with examples.